Amplification of Resonant Rayleigh Light Scattering Response Using Immunogold Colloids for Detection of Lysozyme. Issue 20 (19th April 2013) - Truong, Phuoc Long; Choi, Seung Phill; Sim, Sang Jun
Abstract A strategy for attomolar‐level detection of small molecule‐size proteins is reported based on Rayleigh light scattering spectroscopy of individual nanoplasmonic aptasensors by exploiting the outstanding characteristics of gold colloids to amplify the nontransparent resonant signal at ultralow analyte concentrations. The fabrication method utilizes thiol‐mediated adsorption of a DNA aptamer on the immobilized Au nanoparticle surface, the interfacial binding characteristics of the aptamer with its target molecules, and the antibody–antigen interaction through plasmonic resonance coupling of the Au nanoparticles. Using lysozyme as a model analyte for disease detection, the detection limit of the aptasensor is ∼7 × 103 aM, corresponding to the LSPR λmax shift of ∼2.25 nm. Up to a 380% increase in the localized resonant λmax shift is demonstrated upon antibody binding to the analyte compared to the primary response during signal amplification using immunogold colloids. This enhancement leads to a limit of detection of ∼7 aM, which is an improvement of three orders of magnitude. The results demonstrate substantial promise for developing coupled plasmonic nanostructures for ultrasensitive detection of various biological and chemical analytes.